Socialization of Legal Aid Information System at LBH Hade Indonesia Raya Cibinong Bogor - Haryanto, Haryanto; Wahyudi, Endang; Baidawi, Taufik; Indra, Natal (Edumedia Solution, 2025)
This activity aims to increase the efficiency and accessibility of legal services at LBH Hade Indonesia Raya Cibinong Bogor through the use of digital-based information systems. The main problem faced is the lack of integration of technology in the legal service process, which results in limitations in obtaining legal aid information. Through output targets in the form of increasing accessibility, service efficiency, and increasing internal capacity, the activity plan includes needs analysis, system development, training and implementation, as well as periodic system evaluation and maintenance. Thus, this activity will be a significant breakthrough in efforts to improve legal services in the community